STUDY ON THE INFLUENCE OF POSITIONING STRATEGY, PRODUCT QUALITY, SERVICE QUALITY AND CORPORATE IMAGE TO DECISION OF SAVING AT BANK BJB TEGAL BRANCH - Thauhid, Sandy Baytu; Raharjo, Susilo Toto; Soesanto, Harry (Master of Management Diponegoro University, 2017)
The position of bank bjb based on Total DPK in December 2014 rise to the category national public bank, but it is different from Total DPK in the branch of bank bjb in tegal, in the same period the strategy of bjb Tegal bank accumulate DPK (Dana Pihak Ketiga),by increasing product sales of cheap deposits as well as savings bjb tandamata. This study analyzes several factors that thought to have influence on the decisions to saving, there are: positionong, serving quality, product quality, and corporate image.The population of the respondents in this study as many as 120 customers. In this research using purposive sampling technique.The research results show that the positioning strategy has a positive effect on saving. While the quality of the product has no positive effect against a decision on saving. And quality of the product Â have not a positive effect against the strategy of positioning. The quality of service has a positive influence on the positioning strategy. And the quality of service has a positive effect against the corporate image. And the test results of the corporate image of saving has positive influence. So that it can be summed up in this research decision saving the customer at a bank Branch bjb Tegal is not affected by the quality of the products from the tanda mata bjb savings.